2015
DOI: 10.1007/s00701-015-2646-7
|View full text |Cite
|
Sign up to set email alerts
|

Different clinical course of pallidal deep brain stimulation for phasic- and tonic-type cervical dystonia

Abstract: The clinical outcome of phasic-type cervical dystonia is more favorable than that of tonic-type cervical dystonia following GPi DBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…18 Both neuroimaging and electrophysiological studies have revealed structural and functional network changes in dystonic patients that have resulted in the current opinion that dystonia is a circuit disorder. 42 Although these findings support the notion that suppression of theta activity may be one potential mechanism of pallidal DBS in dystonia, long-term recordings after chronic DBS will have to prove the stability of theta oscillations as recently reported for beta activity in PD. 26 Interestingly, pallidal theta activity was found to be negatively correlated with physiological motor cortical beta and cerebellar alpha band oscillations.…”
Section: Role Of Pallidal Theta Activity In the Pathophysiology Of Dysupporting
confidence: 67%
“…18 Both neuroimaging and electrophysiological studies have revealed structural and functional network changes in dystonic patients that have resulted in the current opinion that dystonia is a circuit disorder. 42 Although these findings support the notion that suppression of theta activity may be one potential mechanism of pallidal DBS in dystonia, long-term recordings after chronic DBS will have to prove the stability of theta oscillations as recently reported for beta activity in PD. 26 Interestingly, pallidal theta activity was found to be negatively correlated with physiological motor cortical beta and cerebellar alpha band oscillations.…”
Section: Role Of Pallidal Theta Activity In the Pathophysiology Of Dysupporting
confidence: 67%
“…5 With conventional cDBS, the clinical improvement of phasic and tonic components differs in time; phasic components improve faster (sometimes even immediately) following the application of DBS, whereas improvement in tonic components can take weeks to months. 11 In contrast, when discontinuing stimulation, phasic components can recur rapidly, while tonic components recur in a more gradual manner. 19 This temporal dissociation leads to the hypothesis that different pathophysiological mechanisms are involved.…”
Section: Phasic and Tonic Components Of Dystoniamentioning
confidence: 99%
“…Furthermore, the mechanism of action of DBS still remains mostly unclear. Previous studies showed immediate effects on oscillatory basal ganglia network activity related to suppression of phasic movements that are also the first to respond to DBS in dystonia . Abnormal posturing usually improves over longer time periods, which is possibly related to functional reorganization of the motor cortex—basal ganglia circuits and plastic changes .…”
Section: Introductionmentioning
confidence: 98%